Recent advances on the molecular mechanisms of exercise-induced improvements of cognitive dysfunction - Yi Lu; Fa-Qian Bu; Fang Wang; Li Liu; Shuai Zhang; Guan Wang; Xiu-Ying Hu (Translational Neurodegeneration, 2023)
Abstract Physical exercise is of great significance for maintaining human health. Exercise can provide varying degrees of benefits to cognitive function at all stages of life cycle. Currently, with the aging of the world’s population and increase of life expectancy, cognitive dysfunction has gradually become a disease of high incidence, which is accompanied by neurodegenerative diseases in elderly individuals. Patients often exhibit memory loss, aphasia and weakening of orientation once diagnosed, and are unable to have a normal life. Cognitive dysfunction largely affects the physical and mental health, reduces the quality of life, and causes a great economic burden to the society. At present, most of the interventions are aimed to maintain the current cognitive level and delay deterioration of cognition. In contrast, exercise as a nonpharmacological therapy has great advantages in its nontoxicity, low cost and universal application. The molecular mechanisms underlying the effect of exercise on cognition are complex, and studies have been extensively centered on neural plasticity, the direct target of exercise in the brain. In addition, mitochondrial stability and energy metabolism are essential for brain status. Meanwhile, the organ-brain axis responds to exercise and induces release of cytokines related to cognition. In this review, we summarize the latest evidence on the molecular mechanisms underlying the effects of exercise on cognition, and point out directions for future research.